IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT USING PICTURE BOOKS AS THE MEDIA - Laraswati, Meilinda; Apriliaswati, Rahayu; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to improve students? reading comprehension of narrative text usingpicture book, especially to improve students? ability in identifying details of story elements, and recognizing words meaning. The writer applied classroom action researchwith three cycles of meetings. The subject was the eighth grade students, in MTs Ika PGAPontianak, academic year 2016/2017. There were 20 students participated in the wholeprocesses. The data from observation checklist and field notes revealed that using picturebook improved students' reading comprehension of narrative text. Picture booksimproved students in recognizing words meaning through pre teaching the words fromthe story prior reading, and the use of picture-text relationship in contextual cluesactivity. Picture books also improved students in identifying story elements through theuse of picture sequences discussion in picture walk activity and story mapping activity.Discussing picture books also promoted students? interest in reading. The scores showedstudents? improvement in recognizing words meaning and story elements. From theresearch, the writer concluded that the use of picture book improved students? ability torecognize words meaning, identify details of story elements and improved students?interest in reading comprehension of narrative text through shared reading with picturewalk, contextual clues, and story mapping.Keywords: Picture books, Narrative text, Reading Comprehension